Integrating Trauma‐Informed Care Into Maternity Care Practice: Conceptual and Practical Issues. (28th November 2017) - Sperlich, Mickey; Seng, Julia S.; Li, Yang; Taylor, Julie; Bradbury‐Jones, Caroline
Abstract: Adverse childhood experiences have a strong negative impact on health and are a significant public health concern. Adverse childhood experiences, including various forms of child maltreatment, together with their mental health sequelae (eg, posttraumatic stress disorder, depression, dissociation) also contribute to adverse pregnancy outcomes (eg, preterm birth, low birth weight), poor postpartum mental health, and impaired or delayed bonding. Intergenerational patterns of maltreatment and mental health disorders have been reported that could be addressed in the childbearing year. Trauma‐informed care is increasingly used in health care organizations and has the potential to assist in improving maternal and infant health. This article presents an overview of traumatic stress sequelae of childhood maltreatment and adversity, the impact of traumatic stress on childbearing, and technical assistance that is available from the National Center for Trauma‐Informed Care (NCTIC) before articulating some steps to conceptualizing and implementing trauma‐informed care into midwifery and other maternity care practices.